2017
DOI: 10.1002/ptr.5782
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Antiviral Properties of Black Elder (Sambucus nigraL.) Products

Abstract: Black elder (Sambucus nigra L.) has a long ethnobotanical history across many disparate cultures as a treatment for viral infection and is currently one of the most-used medicinal plants worldwide. Until recently, however, substantial scientific research concerning its antiviral properties has been lacking. Here, we evaluate the state of current scientific research concerning the use of elderberry extract and related products as antivirals, particularly in the treatment of influenza, as well as their safety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(52 citation statements)
references
References 170 publications
(299 reference statements)
1
49
0
2
Order By: Relevance
“…In addition, phenolic acid constituents of S.ambucus FormosanaNakai, including caffeic acid, caffeotannic acid, chlorogenic acid, coumaric acid, ferulic acid, and gallic acid, have been identified as the members of the most important active components with anti-inflammatory, anti-tumor and anti-hepatotoxic activities (Chen et al, 2001;Liao et al, 2006;Yang and Lin, 2004;Zhang et al, 2010). Active components of Sambucus FormosanaNakai are similar to those of other Sambucus species, including Sambucus nigra L. and Sambucus lanceolata, which process antioxidant, antiradical, antiviral, antimicrobial, and anti-inflammatory activities (Barak et al, 2001;Krawitz et al, 2011;Mandrone et al, 2014;Pinto et al, 2017;Pliszka, 2017;Porter and Bode, 2017;Turek and Cisowski, 2007). Especially, the extract of Sambucus nigra L. exerts the antiviral activity against influenza A and B viruses, human immunodeficiency virus, and the herpes simplex virus type 1 (Krawitz et al, 2011;Serkedjieva et al, 1990;Zakay-Rones et al, 1995;Amoros et al, 1992;Mahmood et al, 1993;Roschek et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In addition, phenolic acid constituents of S.ambucus FormosanaNakai, including caffeic acid, caffeotannic acid, chlorogenic acid, coumaric acid, ferulic acid, and gallic acid, have been identified as the members of the most important active components with anti-inflammatory, anti-tumor and anti-hepatotoxic activities (Chen et al, 2001;Liao et al, 2006;Yang and Lin, 2004;Zhang et al, 2010). Active components of Sambucus FormosanaNakai are similar to those of other Sambucus species, including Sambucus nigra L. and Sambucus lanceolata, which process antioxidant, antiradical, antiviral, antimicrobial, and anti-inflammatory activities (Barak et al, 2001;Krawitz et al, 2011;Mandrone et al, 2014;Pinto et al, 2017;Pliszka, 2017;Porter and Bode, 2017;Turek and Cisowski, 2007). Especially, the extract of Sambucus nigra L. exerts the antiviral activity against influenza A and B viruses, human immunodeficiency virus, and the herpes simplex virus type 1 (Krawitz et al, 2011;Serkedjieva et al, 1990;Zakay-Rones et al, 1995;Amoros et al, 1992;Mahmood et al, 1993;Roschek et al, 2009).…”
Section: Introductionmentioning
confidence: 93%
“…Especially, the extract of Sambucus nigra L. exerts the antiviral activity against influenza A and B viruses, human immunodeficiency virus, and the herpes simplex virus type 1 (Krawitz et al, 2011;Serkedjieva et al, 1990;Zakay-Rones et al, 1995;Amoros et al, 1992;Mahmood et al, 1993;Roschek et al, 2009). Sambucus nigraphenolic acids like caffeic acid show the highly inhibitory effect on the in vitro replication of influenza A virus (Porter and Bode, 2017;Utsunomiya et al, 2014). Since Sambucus FormosanaNakai contains such antiviral active components in the extract of Sambucus nigra L., the antiviral activity of Sambucus FormosanaNakai is worthy to further investigate.…”
Section: Introductionmentioning
confidence: 99%
“…The fruit extract from S . nigra has revealed efficacy in treating numerous viral infections (Porter and Bode, ). S .…”
Section: Medicinal Plants Used In Influenzamentioning
confidence: 99%
“…The berries and flowers of this plant are reported from different cultures for the treatment of various viral infections. Studies revealed that there is no any cyanide compound in flowers and berries responsible for the treatment of viral infections (Porter and Bode, ). S .…”
Section: Medicinal Plants Used In Influenzamentioning
confidence: 99%
See 1 more Smart Citation